Molecular Alterations in Pulmonary Adenocarcinoma of African Americans - Erika F. Rodriguez (2019)
© American Society for Clinical Pathology, 2019. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com. OBJECTIVES: Identify molecular alterations in pulmonary adenocarcinoma (ADC) in African American (AA) patients diagnosed on cytology specimens. METHODS: After institutional review board approval, we searched our database from 2013 to 2017 for AA patients with a diagnosis of pulmonary ADC. Molecular and clinical data were reviewed. White patients also diagnosed with pulmonary ADC on cytology samples formed a control group. RESULTS: A total of 113 patients were identified. Mean age was 63.4 years. Molecular tests were available for 91 patients. Mutations were identified in 53 (58.2%) cases. The most common mutations were EGFR (n = 19 cases, 36%) and KRAS (n = 24 cases, 45%). When compared with whites, AA patients were diagnosed at higher stages (P = .045) and demonstrated shorter overall survival (17 vs 47 months, P = .0150). No differences were noted regarding distribution of molecular alterations. CONCLUSION: AA patients have similar molecular alterations in ADCs as their white counterparts. However, they have worse outcomes.